Update on monoclonal gammopathy of renal significance [Neues zur monoklonalen Gammopathie renaler Signifikanz] - Büttner-Herold, Maike; Pfister, F.; Amann, Kerstin Ute (Nephrologe, 2019)
The term monoclonal gammopathy of renal significance (MGRS) was recently introduced for glomerular or tubulointerstitial renal diseases that are induced by a monoclonal immunoglobulin (MIg) in the setting of a monoclonal gammopathy of uncertain significance (MGUS) which is regarded as a benign condition. Most of these MIg-associated renal diseases result from direct deposition of nephrotoxic immunoglobulins or their fragments, i. e. light and heavy chain fragments. Hereby, the nature and exact location of the immunoglobulin deposition defines the disease so that apart from light microscopy, immunohistochemistry and/or immunofluorescence and electron microscopy are of utmost importance in the workup of kidney biopsies. It is assumed that at least some members of the MGRS group of diseases, irrespective of the underlying disease, are associated with a higher progression rate which may be one reason for MGRS being considered as an indication for antineoplastic therapy.
CRIS-Team Scopus Importer:2019-05-03
Keywords: Biopsy; Electron microscopy; Immunohistochemistry; Kidney; Paraproteinemias